TA’LIL AHKAM DAN IJTIHAD KONTEKSTUAL DALAM PEMBINAAN HUKUM ISLAM - Imran Abubakar (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2013)
Ta’lil Ahkam is an actualization methodology Shari'ah values in practicallife. Ta’lil Ahkam acceptance in the science of jurisprudence has been thecornerstone of ijtihad contextual acceptance. Blend the concept of contextualTa’lil Ahkam and Ijtihad in Islamic law coaching will give birth to a law that canrun at any time. Opposition in Ta’lil Ahkam acceptance in the knowledge ofKalam, should not be used as a first principle to prove that scholars are not ijma(agreed) to Ta’lil Ahkam acceptance in the jurisprudence.